Reaffirming the Scientific Purpose of Medical Journals: Concerns over The Lancet’s Coverage of Indian Medical Education - Rana , Rishabh Kumar; Joshi, Krupal J; Singhal, Sanjay; Kapil, Umesh (Indian Journal of Community Health, 2025)
We express grave concern over the Editorial "Corruption scandal engulfs Indian medical education" published in The Lancet on July 19, 2025 (1). We hold The Lancet's prestigious global reputation and historical contributions to medical science in high regard. Still, we critically question its editorial judgment and adherence to the journal's core scientific goals in publishing this article. Our criticisms arise from these five essential and interconnected issues: Essential Discrepancy with Scientific Purpose: The Lancet's stated goal, according to our understanding and the general global view, is the "promotion and dissemination of advancements in Medical Sciences." However, this article focuses on unsubstantiated criminal accusations against specific individuals (1), rather than presenting scientific research, clinical data, or medical progress. Investigative journalism, particularly on alleged corruption and legal issues, falls clearly within the domain of news organizations, not a leading scientific journal. Publishing such material blurs important disciplinary boundaries, threatens The Lancet's unique scientific credibility, and significantly diverges from the strict standards of evidence-based reporting expected from a scientific journal.